The Effect Of Action Learning Strategy In Improving Students’ Speaking Skill At Mts Nw Husnul Abror Graders - Muliadi, Mul; lestari, baiq santika (JUPE : Jurnal Pendidikan Mandala, 2024)
English. Students still difficult to pronounce a word or sentences, confused and lack self confident to speak out because they were worried about the mistakes. This is caused by the lack of vocabulary and other factors. To solve this problem the researcher did the research by action learning strategy in teaching speaking. The Objective of this research was to get empirical evidence about The Effect of Action Learning Strategy on Students‟ Speaking Ability. This research used pre- experimental method. This research had been conducted at MTs NW Husnul Abror. The Population of this research was the eighth-grade students which consisted of 32 students. In taking the sample, the present researcher used simple random sampling technique. The class taken was VIII. To collect the data, pre test and post test were given to the 32 students. It aimed at determined the mean score, standard deviation, normality, homogeneity, and hypothesis testing. Based on the data analysis, the present researcher found that the mean score of pre test was 55.25 and post test was 79.47. It indicated that in hypothesis testing, T test < α = 0.05 (0.000 < 0.05). It meant that the alternative hypothesis was accepted and the null hypothesis was rejected. It can be concluded that action learning strategy was significantly effective in improving students’ speaking skill at the eighth grader of MTs NW Husnul Abror